1998
DOI: 10.1007/s004150050239
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological brain stem investigations in idiopathic narcolepsy

Abstract: Narcolepsy is associated with various rapid eye movement (REM) sleep abnormalities. Distinct brain stem areas seem to play a prominent role in REM sleep regulation. Recent magnetic resonance imaging (MRI) studies have led to conflicting findings concerning the presence of structural brain stem lesions in patients with idiopathic narcoleptic syndrome. However, multimodal electrophysiological brain stem investigations may reveal functional brain stem abnormalities even in the absence of MRI abnormality. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…This is in line with existing literature showing, at least in the cataplexy‐free state, no difference in blink reflex in narcolepsy–cataplexy compared to controls (Khatami et al. , 2007; Marx et al. , 1998).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with existing literature showing, at least in the cataplexy‐free state, no difference in blink reflex in narcolepsy–cataplexy compared to controls (Khatami et al. , 2007; Marx et al. , 1998).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, blink reflex parameters did not differ between patients and controls. This is in line with existing literature showing, at least in the cataplexy-free state, no difference in blink reflex in narcolepsy-cataplexy compared to controls (Khatami et al, 2007;Marx et al, 1998). In addition, Khatami et al (2007) found that patients with narcolepsy-cataplexy failed to exhibit startle potentiation during unpleasant stimuli, supporting the hypothesis of an amygdala dysfunction in human narcolepsy-cataplexy.…”
Section: Discussionsupporting
confidence: 90%
“…However, Overeem et al [28] found no differences in global gray or white matter volumes between patients and controls, suggesting either that narcolepsy is associated with microscopic changes undetectable by VBM or that functional abnormalities of hypocretin neurons do not have any structural correlates. A multimodal electrophysiological investigation showed no relevant brain stem lesions as compared with controls [24].An attempt to utilize quantitative EEG methods for assessing EDS in narcolepsy had been made before by Alloway et al [1], who applied the alpha attenuation test (AAT). In a power spectral analysis of a single EEG lead it was found that mean eyes-closed alpha power was significantly reduced in narcoleptics as compared to normals.…”
Section: Discussionmentioning
confidence: 98%